(untitled) (Patan Prospective Journal, 2024)
This article examines the impact of strategies in mitigating the risk in commercial banks of Nepal. First the paper introduces the risk in the financial institutions and then discusses the types of risks in the banks that rely on the IT systems for the operations and services. Besides, it forwards some strategies that can help the banking sector to reduce the risk and to promote the security from the attackers. I have used the mixed method of research design and have massively used the secondary data to assess the impact of the tools and techniques employed in mitigating the risk in the banking sector of Nepal. Despite the reliance on the secondary materials for information, the paper is analytical and critical contribution to the existing knowledge on the subject i.e. the risk management in the financial institutions of Nepal. The major objective of the paper has been to scrutinize the current risks faced by the banks in Nepal and the process of reducing the risks as adopted by the financial institutions in general. The finding of the study is the spread of awareness and updating the IT systems by the banks can help to protect the systems from the intruders and the cyber security must be strengthened to let the financial institutions feel safe.